1991
DOI: 10.1016/0020-7292(91)90812-j
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the management of low risk obstetric patients

Abstract: Specific interventional procedures have enjoyed widespread popularity in the United States in the routine management of low risk obstetric patients without the benefit of clinical studies attesting to their utility. A review of the literature was conducted to survey obstetric practice with regard to amniotomy, intravenous fluids, third stage administration of oxytocics, episiotomy and continuous fetal monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Women giving birth by normal vaginal delivery may have either episiotomy or spontaneous laceration or both. Episiotomy is carried out in these women to decrease the rate of spontaneous laceration (Thorp & Bowes 1989, Davis & Riedmann 1991, Fernando et al. 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Women giving birth by normal vaginal delivery may have either episiotomy or spontaneous laceration or both. Episiotomy is carried out in these women to decrease the rate of spontaneous laceration (Thorp & Bowes 1989, Davis & Riedmann 1991, Fernando et al. 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in the literature that episiotomy prevents weakness of perineal muscle and thus development of stress incontinence (Davis & Riedmann 1991, Bobak & Jensen 1993). In our study, it was found that mothers in the episiotomy group had a lower rate of urinary incontinence than those in the control group, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the most common operation in obstetrics, with 50% of vaginal births in the United States still accompanied by episiotomy (2). Several meta analyses in the past decade have assessed the legitimate place of routine episiotomy in obstetric practice (3–5). Although episiotomy may be indicated to shorten the second stage of labor for reasons of maternal or fetal distress, no data support any short‐ or long‐term health benefits of routine episiotomy.…”
mentioning
confidence: 99%
“…As pesquisas mostram que a adoção de procedimentos desnecessários ou inadequadamente utilizados, como amniotomia precoce, infusão endovenosa de ocitocina e analgesia, alteram o curso fisiológico do parto e desencadeiam uma cascata de eventos, em que uma intervenção condiciona a outra. Com isso, elevamse progressivamente o nível de complexidade dos procedimentos e o risco obstétrico e perinatal (1,5) .…”
Section: Introductionunclassified